The effectiveness of baking soda as a polishing agent for tooth surfaces - De Guzman, Jocelyn L.; Mojica, Marjorie A.; Murjani, Bhabita (Adviser).
Pumice is a widely accepted abrasive agent used by dental practitioners for polishing tooth surfaces after scaling. However, baking soda, a more commonly available abrasive may be an option for those in provincial areas. This study aimed to compare baking soda to pumice as to its effectiveness as a polishing agent, particularly in its ability to smoothen roughened enamel surface. Seventy-four randomly selected tooth samples were prepared by wet grinding using water-resistant silicone carbide paper and divided into four batches. One batch was polished with pumice slurry for 5 seconds, another for 10 seconds. The third batch was subjected to baking soda slurry for 5 seconds and the fourth batch for 10 seconds. Rubber cups were used for polishing, after which, the teeth were sectioned. The depth of scratches were then measured in microns using the scanning electron microscope (SEM). The mean depth obtained using baking soda for 5 seconds was 1.46 microns and for 10 seconds, the mean depth was 1.45 microns. On the other hand, the mean depth obtained using pumice for 5 seconds was 2.08 microns while for 10 seconds, the mean depth was 2.06 microns. Using the analysis of variance at P<0.050, results showed that baking soda is more effective than pumice in polishing tooth surfaces since the mean depth of scratches is shallower compared to pumice.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.